(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research examined the industry 4.0 business environment, management techniques, and service strategies of small and medium-sized electronic component makers. Using a questionnaire, 350 Thai electrical components executives and entrepreneurs provided data. Analyses included frequency, percentage, mean, standard deviation, and factor analysis. The study’s majority of respondents were men aged 36–40 with a Bachelor of Business Administration degree. They averaged 11–15 years in the firm. These entrepreneurs distributed electronic components with overseas partners. Their enterprises have 51–100 employees and 6–8 million baht in assets. They exported 1–10% of their goods and imported 1–10% of their raw materials. The firms performed worse than last year. These companies’ management strategy factors averaged 4.0. Work satisfaction, economy, quality, command, planning, coordination, just-in-time, and technology were the most important aspects, in order. Control and management were relatively significant. The research found five main components and twenty-five subcomponents of Industry 4.0 management strategies for small and medium-sized electronic component makers. These include organizational quality management, cost-effective planning, coordination, command, and control.